(untitled) (Anais do Congresso Brasileiro de Processo Coletivo e Cidadania, 2024)
The study explores collective protection as a tool for safeguarding and affirming fundamental rights in the current society of risk, as defined by the German sociologist Ulrich Beck. It analyzes the role of collective rights and their procedural means of defense in mitigating and alleviating the growing risks and threats in the present context, characterized by the widespread sharing and distribution of dangers, regardless of location and social condition, stemming from the development of production forces. The research is justified and grounded in the appreciation of collective processes, recognizing them as a viable and effective tool for protecting the fundamental rights of individuals and for achieving constitutional principles of human dignity (Article 1 of the Brazilian Constitution of 1988) and social justice (Article 3 of the Brazilian Constitution of 1988). The methodology employed is bibliographical research, relying on relevant authors who discuss the subject. Furthermore, it adopts an exploratory approach, involving the analysis of legal texts and emblematic cases. Keywords: Fundamental Rights. Society of Risk. Collective Protection.